Negros laços: trajetórias coletivas das famílias dos nascidos de Ventre Livre no pós-abolição (Santa Maria/RS, 1871-1941) - Oliveira, Franciele Rocha de (2023)
This work constitutes a study of black families in the post-Abolition period in southern Brazil and encompasses the analysis of the experiences of those born with free wombs in the city of Santa Maria da Boca do Monte, located in the central region of Rio Grande do Sul. It deals with the experiences of children born to enslaved mothers, born between 1871 and 1888 in that city and baptized by the Catholic Church, whose experiences were impacted by Law number 2.040, of September 28, 1871. It presents an analysis of the living conditions of these children and the families they started to form in the post-Abolition period, between the years 1890 and 1941, through civil and religious marriages and the creation of different family ties, analyzed by this research. The work uses as a theoretical-methodological contribution to microhistory and the onomastic method or research centered on names, located in different sources and contexts to trace collective trajectories, social relations and genealogies, combining the use of serial history, which allowed observe patterns, inconsistencies and singularities of collective and generational experiences between slavery and freedom. 532 children born from a free womb were located, of which 89 or 17% of the baptized children who survived to adulthood were found, when they started to form their own families, through the analysis of various civil-notary and parish records. Oral sources were also used, through Oral History as a method for reconstituting black families, their relationships and their memories of slavery and freedom. Thus, grandchildren and granddaughters of those born in Free Womb whose baptisms and marriages were located were interviewed. The results of this research point to original conclusions about the study of black families in the post-Abolition period, presenting reflections on their plural family organizations and their found kinships, their ways of naming, inheriting and bequeathing, living and inhabiting and, mainly, getting married.